PILKADA: PERSPEKTIF POLITICKING. PARADIGM SHIFT, ORGANIZATIONAL BEHAVIOR DAN IMPLIKASINYA PADA PENINGKATAN KINERJA SDM - Ristianni, Erwina - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2005)
Abstract It seems that currently the word â€œPilkadaâ€ (regional head election) sounds familiar to the society. They understand that Pilkada is democratic medium for electing governor, regent mayor and their deputies. And interesting matter to study in this first ever Indonesia regional head election, which is also one of the reform agendas, is that there are changes of organization, culture, attitude and leadership as well as human resources. The shift on the assumptions is considered normal as now days people become more and more intelligent, have realistic demands and transform to the needs of better productivity. The paradigm shift requires the use of special strategy to win the election. The strategy to win in the regional head election brings a consequence of how the candidates do politicking toward factors so that they work more professionally and clean from corruption, collusion and nepotism. Keywords: Pilkada, Politicking, Paradigm Shift, OrganizationalÂ  Behavior, HR Performer